2016
DOI: 10.2134/jeq2015.12.0596
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biomass Crops Using Biowastes on Low‐Fertility Soil: 1. Influence of Biowastes on Plant and Soil Quality

Abstract: Land application of biosolids to low-fertility soil can improve soil quality by increasing concentrations of macronutrients and trace elements. Mixing biosolids with sawdust could reduce the risks of contaminant accumulation posed by rebuilding soils using biosolids alone. We aimed to determine the effects of biosolids and biosolids-sawdust on the plant quality and chemical composition of sorghum, rapeseed, and ryegrass. Plants were grown in a greenhouse over a 5-mo period in a low-fertility soil amended with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…Our findings additionally underlined the fact that the application of a single high rate in three years (B15) is prone to increased risks of leaching as compared to a yearly application (B5), which in turn was proved to be not upsetting and certainly comparable to conventional mineral fertilization, as already reported by previous research [11,[70][71][72].…”
Section: Type and Rate Of Fertilizers Can Affect Nitrate Leaching Risksupporting
confidence: 85%
“…Our findings additionally underlined the fact that the application of a single high rate in three years (B15) is prone to increased risks of leaching as compared to a yearly application (B5), which in turn was proved to be not upsetting and certainly comparable to conventional mineral fertilization, as already reported by previous research [11,[70][71][72].…”
Section: Type and Rate Of Fertilizers Can Affect Nitrate Leaching Risksupporting
confidence: 85%
“…Biowastes can increase soil carbon (Wang et al, 2008). Through the processes of immobilization and sorption, this carbon may increase plant available N, P, K, and S (McLaren and Cameron, 1996) unless these elements are present in high concentrations in the biowaste itself (Esperschuetz et al, 2016). Most landbased municipal wastewater sites in NZ have low initial carbon contents, so they respond to relatively moderate levels of biowaste additions.…”
Section: Influence Of Biowastes On Soil Carbon and Nutrientsmentioning
confidence: 99%
“…In the latter, microbe-extraction of N can be so effective that plant growth is suppressed. For example, blending 3 t/ha sawdust with 1,250 kg N/ha biosolids reduced ryegrass biomass by about 25% compared with unamended municipal biosolids (Esperschuetz et al, 2016). High inorganic N in biowastes can also enhance TE mobility, particularly Zn and Cd, which have less affinity for organic matter than Cr and Pb (Smith et al, 1992).…”
Section: Influence Of Biowastes On Soil Carbon and Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heller et al (2003) suggested that using biosolids instead of synthetic fertilizer for willow production would increase energy conversion efficiency of cellulosic based biofuel by eliminating synthetic fertilizers. Esperschuetz et al (2016) observed improved yields and seed production of biomass crops with biosolid applications to low-fertility soils, compared to urea.…”
Section: Introductionmentioning
confidence: 94%